Birds of prey - Stone, Lynn M. (Chicago : Childrens Press, 1983)
Briefly discusses the physical characteristics and habits of owls, vultures, hawks, and eagles.
Includes index.
Keywords: Birds of prey -- Juvenile literature; Birds of prey